STRENGTHENING POLITICAL PARTY IN INDONESIA THROUGH FUNDING FROM THE NATIONAL STATE BUDGET - Bagus Priyo Prasojo (FH 16 UMY 076, 2016)
Minister of Home Affairs, Tjahjo Kumolo recently unveiled a plan to increase annual funding to a maximum of IDR 1 trillion for each political party, a plan that could be feasible within five years, after the 2019 elections. The increasing of state funding for political parties is expected to support political parties a pillar of democracy and repair the image of politicians. The support currently allocated by the state is about IDR 108 per-valid vote to every party, and cannot comply with the need of huge political cost of political parties. The research aims to assess whether the political party funding allocated by the Government through National State Budget may strenghten the political party. The research is doctrinal research which uses a qualitative method. This paper provides an in-depth analysis and a critical examination on political party in details pertaining to the role of the Political party in Indonesia, the needs to increase the government allocation, and the challenges of the increasing of the allocation. The result of research shows that the funding of the political party through the National State Budget may strengthen the political party in Indonesia. Besides allocating the National State Budget for funding the political party annually, Indonesia should also strengthen the supervision of political party in terms of the accountability of the use of fund in carrying out its functions annually. Political Parties should have a clear commitment, transparency of income and expenditure and there should be firm sanctions on the political party that violates the laws. Key words: Political party, funding, democratic practice, Political corruption